Structure and functionalities of the human c-reactive protein compared to the zebrafish multigene family of c-reactive-like proteins. (April 2017) - Bello-Perez, Melissa; Falco, Alberto; Medina, Regla; Encinar, Jose Antonio; Novoa, Beatriz; Perez, Luis; Estepa, Amparo; Coll, Julio
Abstract: Because of the recent discovery of multiple c-reactive protein ( crp )-like genes in zebrafish ( Danio rerio ) with predicted heterogeneous phospholipid-binding amino acid sequences and heterogeneous transcript expression levels in viral survivors and adaptive-deficient mutants, zebrafish constitute an attractive new model for exploring the evolution of these protein's functions, including their possible participation in fish trained immunity. Circulating human CRP belongs to the short pentraxin family of oligomeric proteins that are characteristic of early acute-phase innate responses and is widely used as a clinical inflammation marker. In contrast to pentameric human CRP (pCRP), zebrafish CRPs are trimeric (tCRP); however monomeric CRP (mCRP) conformations may also be generated when associated with cellular membranes as occurs in humans. Compared to human CRP, zebrafish CRP-like proteins show homologous amino acid sequence stretches that are consistent with, although not yet demonstrated, cysteine-dependent redox switches, calcium-binding spots, phosphocholine-binding pockets, C1q-binding domains, regions interacting with immunoglobulin Fc receptors (FcR), unique mCRP epitopes, mCRP binding peptides to cholesterol-enriched rafts, protease target sites, and/or binding sites to monocyte, macrophage, neutrophils, platelets and/or endothelial cells. Amino acid variations among the zebrafish CRP-like multiprotein family and derived isoforms in these stretches suggest that functional heterogeneity best fits the wide variety of aquatic pathogens. As occurs in humans, phospholipid-tagged tCRP-like multiproteins might also influence local inflammation and induce innate immune responses; however, in addition, different zebrafish tCRP-like proteins and/or isoforms might fine tune new still unknown functions. The information reviewed here could be of value for future studies not only to comparative but also medical immunologists and/or fisheries sectors. This review also introduces some novel speculations for future studies. Abstract : Human/zebrafish CRP-like protein studies are compared. Zebrafish multi-gene families, structures and expression microarray results are revised. Novel functionalities of one-gene human monomeric conformations are reviewed. New explorations are proposed for future studies.